Sharī’a, Fiqh, and Qānūn: A Portrait of the Cognitive Nature of Islamic Law in Indonesia - Hakim, Muhammad Lutfi (UIN Sunan Kalijaga, 2021)
Abstract: This article examines the cognitive nature of Islamic law in Indonesia, particularly regarding understanding and applying the terminology of Sharī’ah,fiqh, and qānūn in several scientific works by Indonesian Muslim scholars and Regional Regulations Aceh Darussalam.Using the cognitive nature theory of Jasser Auda, it is concluded that there are significant differences between Sharī’ah, fiqh, and qānūn from the creator, source, scope, nature, time, amount, and characteristics. However, some Indonesian Muslim academics, legislators, and scholars often use the terms Sharī’ah, fiqh, and qānūn interchangeably and include them in the realm of absolute divine revelation. Therefore, the three times are often used interchangeably and sometimes overlap. That matter can be seen in many articles from some Indonesian Muslim intellectuals and in the regional regulation on Islamic Sharī’ah in Aceh, which legislators formulated. As a result, fiqhand qānūn, which are products of human thought from the effects of their understanding of the Qur’an and hadith as God’s revelations, are considered to have absolute truth like the Qur’an and hadith itself.Abstrak: Artikel ini mengkaji watak kognitif hukum Islam Indonesia, khususnya terkait pemahaman dan penggunaan terminologi syari’ah, fikih dan kanun dalam sejumlah karya ilmiah para sarjana muslim Indonesia dan juga Peraturan Daerah di Aceh Darussalam. Dengan mempergunakan teori watak kognitif Jasser Auda, diperoleh kesimpulan bahwa terdapat perbedaan yang signifikan antara syariah, fikih, dan kanun dari aspek kreator, sumber, ruang lingkup, sifat, waktu, jumlah, dan karakteristiknya. Namun demikian, sebagian sarjana Muslim Indonesia, legislator dan para ulama sering menggunakan terma syari’ah, fikih dan kanun secara sama dan memasukannya ke dalam wilayah wahyu Tuhan yang bersifat absolut. Oleh karena itu, ketiga terma tersebut sering digunakan secara bergantian dan adakalanya juga tumpang tindih. Hal tersebut terlihat dalam sejumlah artikel dari sebagian sarjana Muslim Indonesia dan Perda Syari’ah Islam di Aceh yang dirumuskan oleh para legislator. Akibatnya, fikih dan kanun yang merupakan produk pemikiran manusia dari hasil pemahamannya atas Al-Qur’an dan as-Sunnah sebagai wahyu Tuhan dinilai memiliki kebenaran absolut layaknya Al-Qur’an dan as-Sunnah itu sendiri.